Pelanggaran Hukum Terhadap Hak Cipta Lagu Karena Melakukan Perubahan Secara Ilegal - Ndokii, Pongki Paulus; Yunanto, Yunanto (Fakultas Syariah INSURI Ponorogo, 2023)
Copyright is the exclusive right of the creator that arises automatically based ondeclarative principles after a work is realized in a tangible form without reducingrestrictions in accordance with the provisions of laws and regulations. Thedefinition of Copyright is regulated in Law Number 28 of 2014 concerningCopyright Article 1 number 1. Copyright is different from other IntellectualProperty Rights which must be registered. Copyright does not protect ideas,information or facts. Copyright begins with the existence of an idea which is thenrealized in a tangible form. The idea that has been realized in a tangible form thengets exclusive rights automatically. There are two types of exclusive rights,namely moral rights and economic rights. Moral rights are the rights ofindividuals or individuals to the copyrighted works they produce not to bechanged by anyone, even though the copyright of the work has actually beenhanded over to other parties. Economic rights are the exclusive rights of thecreator or copyright holder to obtain economic benefits from the work. But infact, there are still many people who commit copyright infringement withoutpaying attention to the moral rights and economic rights of the creator orcopyright holder. At this time technology has developed rapidly and committinga copyright infringement has been easy to do with the development oftechnology. Especially the act of copying product photos that occur on theinternet, namely Instagram social media. This raises the question of whether theact of copying product photos on social media is a violation of copyright andwhat are the legal remedies.